DOES GERONTOPSYCHIATRY BELONG TO MEDICINE? CROSS-SECTIONAL STUDY MONITORING POLYMORBIDITY IN HOSPITALIZED GERONTOPSYCHIATRIC PATIENTS - Luzny, Jan; Bellova, Jana; Donek, Emanuel (Biomedical papers, 2010)
Background: A cross-sectional study has been designed and the study observes the prevalence of polymorbidity in senior inpatients suffering from psychiatric morbidity hospitalized in gerontopsychiatric ward in one of the biggest psychiatric hospitals in the Czech Republic. The aim of the study is to prove that gerontopsychiatry is a comprehensive specialization for both doctors and nurses and should not be viewed as a low-status medical specialization.Methods and results: A cross-sectional study comprising of 304 patients was designed and a simple descriptive analysis of the patients' medical records was carried out. Polymorbidity and serious somatic conditions were present in senior patients hospitalized in gerontopsychiatric ward. Polypharmacy is a widespread phenomenon and has hazardous side effects for the treatment of patients. Last but not the least it also makes the treatment more expensive.Conclusion: Both doctors and nurses working in gerontopsychiatry should have a comprehensive interdisciplinary knowledge that would help in both early detection of many serious somatic conditions and in the improvement of the reputation of gerontopsychatry.
Keywords: Gerontopsychiatry/Polymorbidity/Polypharmacy